Implementing Health Financing Reforms in Africa: Perspectives of Health System Stewards - Tom Achoki; Abaleng Lesego (Ubiquity Press, 2017)
Background A majority of health systems in the sub-Saharan Africa region are faced with multiple competing priorities amid pressing resource constraints. Health financing reforms, characterized by expansion of health insurance coverage, have been proposed as promising in the quest to improve health sustainably. However, in many countries where these measures are being attempted, their broader implications have not been fully appreciated. Methods This study was based on perspectives of 37 health system stewards from Botswana who were interviewed in order to understand opportunities and challenges that would result in the quest to expand health insurance coverage in the country. Thematic synthesis of their perspectives, focusing on the key aspects of the health systems, was done in order to draw informative lessons that could be applicable to a broader set of low- and middle-income countries. Findings Health systems attempting to expand health insurance coverage would be faced with various opportunities and challenges that have implications on performance. By increasing the pool of resources available to spend on health, health insurance would afford health systems the opportunity to increase population access to and use of health services. However, if unchecked, this could also translate to uncontrolled demand for expensive medicines and other health technologies, leading to cost escalation and inefficiencies within the system. Therefore, the success of any health financing reform is dependent on embracing sound policies, regulations, and accountability measures. Conclusions Health financing reforms have broader implications to health system performance that should be fully appreciated and anticipated before implementation. Therefore, health system leaders who are keen to improve health must view any health financing reforms through the broader framework of the health system framework in order to make progress.